Shredheads go mainstream? Snowboarding and alternative youth - Humphreys, D. E.. (International Review for the Sociology of Sport, 1997)
This article analyses how a number of postwar shifts in the social mood, or zeitgeist, have influenced the alternative youth culture of snowboarding. It is argued that although snowboarding provides consumer capitalism with a new source of styles and images to exploit, its market-driven popularity also enables snowboarders to create social spaces in which they retain many of the unique philosophies of alternative youth, such as cooperation, fun and freedom.